Gamification Approach in Teaching and Learning - Mohd Zahari, Noorul Amilin; Hasni, Nabilah Safra (Journal of Computing Technologies and Creative Content, 2019)
This paper presents a research about gamification approach in teaching and learning. The main purpose is to identify the effectiveness of using gamification in teaching and learning process.